Hydrodynamics and sediment dynamics in Barataria Bay, Louisiana, USA. (5th February 2021) - Li, Guandong; Xu, Kehui; Xue, Z. George; Liu, Haoran; Bentley, Samuel J.
Abstract: Barataria Bay is a receiving basin for a large Mid-Barataria Sediment Diversion scheme in Louisiana, USA. In this region, data on sediment transport and hydrodynamics are scarce but essential for the design and planning of future sediment diversion and marsh creation. Four months of bottom boundary layer observations were conducted to study winter and spring hydrodynamics and sediment dynamics in this coastal bay. Hourly waves, tides, currents, and bottom suspended sediment concentrations were measured using multiple optical and acoustic sensors attached to two tripod platforms. High temporal resolution data indicated that the salinity in the northern bay was mainly controlled by northerly winds, and tidal currents kept the salinity high in the southern bay during the winter cold front season. In spring, frequent, pervasive southerly winds and the westward shelf transport of less saline water emerging from the Mississippi River Delta lowered the salinity in the southern bay. Spectral analysis showed that wave-current combined shear stress played the most critical role in triggering sediment resuspension. The Style-Glenn 1-D bottom boundary layer model was applied in sediment flux calculations, and showed that net sediment transport mainly occurred during cold front passages. During two 3-day cold-front events, southward sediment fluxes accounted for 56% of the total sediment flux during the 35-day winter period, revealing their nonlinear, event-driven, and episodic nature. The direction of the sediment transport generally rotated, and its magnitude changed considerably, when southeasterly winds shifted to intensified northwesterly winds. Long-duration southerly pre-frontal winds facilitated wetland sedimentation by transporting sediment to the northern bay during high water level conditions impacted by flooding spring tides or southerly winds. Conversely, northerly winds during cold fronts dominated bidirectional tidal currents and led to southward net sediment transport and possible escape of sediment from the bay. The timing of diversion openings, the orientation of receiving basins, and dominant wind directions in relation to fetch, as well as the dynamic water levels should be considered in the planning and management of future diversion operations in coastal areas. Highlights: First long-term time-series BBL observational research conducted in Barataria Bay, Louisiana, USA. Rotational sediment transport was captured in 2019 spring observational period. Sediment transport mainly occurred with cold front passage. Special morphology, such as tidal channel, can strengthen tidal impacts on sediment dynamics in microtidal area.